Diversification Products and Digital Marketing as Innovation and Creativepreneurship Smart Farming Community Karangpucung Village - Mulasiwi, Cut Misni; Puspasari, Elsa; Noorhidayah, Ratri; Triyono, Bambang (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Karang Pucung Village, located in the lowlands of Purbalingga Regency, has great potential for fruit and vegetable farming. Agricultural innovation has been developed by millennial farmers, especially in melon cultivation. Since 2015, farmers organized under the ARTANSI CANDRA KAHURIPAN Tourism Awareness Group (POKDARWIS) have cultivated melons using hydroponic methods. This initiative responds to the increasing national demand for fruits and vegetables and growing health awareness. However, the main problems faced by partners include a lack of knowledge in agricultural product processing, packaging, and marketing. These limitations hinder the optimal utilization of melon harvests. Additionally, partners struggle with online marketing and bookkeeping. Proper accounting is essential for running a sustainable business, yet partners have not implemented systematic and detailed financial recording either manually or digitally. To address these issues, participatory training and mentoring methods are proposed. This approach involves partners directly in each step of the process, including problem identification, analysis of possible actions, action planning, and implementation. This “bottom-up” method ensures that the actions taken are appropriate, targeted, and practical for addressing real problems faced by the community. The result of this community service activity is the ability of local farmers to process melons into melon chips, a product with market potential at both the local and national levels. Through this approach, the community not only enhances its economic value but also strengthens its business practices in packaging, marketing, and financial management, promoting sustainability and independence in the agricultural sector.